Impairment of Sulfite Reductase Decreases Oxidative Stress Tolerance in Arabidopsis thaliana - Wang, Meiping; Jia, Yunli; Xu, Ziwei; Xia, Zongliang (Frontiers in Plant Science, 2016)
As an essential enzyme in the sulfate assimilation reductive pathway, sulfite reductase (SiR) plays important roles in diverse metabolic processes such as sulfur homeostasis and cysteine metabolism. However, whether plant SiR is involved in oxidative stress response is largely unknown. Here, we show that SiR functions in methyl viologen (MV)-induced oxidative stress in Arabidopsis. The transcript levels of SiR were higher in leaves, immature siliques, and roots and were markedly and rapidly up-regulated by MV exposure. The SiR knock-down transgenic lines had about 60% residual transcripts and were more susceptible than wild-type when exposed to oxidative stress. The severe damage phenotypes of the SiR-impaired lines were accompanied by increases of hydrogen peroxide (H2O2), malondialdehyde (MDA), and sulfite accumulations, but less amounts of glutathione (GSH). Interestingly, application of exogenous GSH effectively rescued corresponding MV hypersensitivity in SiR-impaired plants. qRT-PCR analysis revealed that there was significantly increased expression of several sulfite metabolism-related genes in SiR-impaired lines. Noticeably, enhanced transcripts of the three APR genes were quite evident in SiR-impaired plants; suggesting that the increased sulfite in the SiR-impaired plants could be a result of the reduced SiR coupled to enhanced APR expression during oxidative stress. Together, our results indicate that SiR is involved in oxidative stress tolerance possibly by maintaining sulfite homeostasis, regulating GSH levels, and modulating sulfite metabolism-related gene expression in Arabidopsis. SiR could be exploited for engineering environmental stress-tolerant plants in molecular breeding of crops.